Mechanics of Materials An Introduction to Engineering Technology - Ghavami, Parviz. (Springer International Publishing : Imprint: Springer, 2015)
This book, framed in the processes of engineering analysis and design, presents concepts in mechanics of materials for students in two-year or four-year programs in engineering technology, architecture, and building construction, as well as for students in vocational schools and technical institutes. Using the principles and laws of mechanics, physics, and the fundamentals of engineering, Mechanics of Materials: An Introduction for Engineering Technology will help aspiring and practicing engineers and engineering technicians from across disciplines—mechanical, civil, chemical, and electrical—apply concepts of engineering mechanics for analysis and design of materials, structures, and machine components. The book is ideal for those seeking a rigorous, algebra/trigonometry-based text on the mechanics of materials. This book also: · Elucidates concepts of engineering mechanics in materials, including stress and strain, force systems on structures, moment of inertia, and shear and bending moments in a beam without requiring a background in calculus · Illustrates the influence of mechanical properties of materials using real engineering problems · Serves as a valuable reference for students and practitioners seeking state licensing in professional engineering · Includes appendices of useful standard material properties, diagrams, and formulas readers need for calculation and design purposes · Reinforces concepts presented with student exercises.